Insulin degludec: Overview of a novel ultra long-acting basal insulin - Gough, S; Harris, S; Woo, V; Davies, M (2013)
All the basal insulin products currently available have suboptimal pharmacokinetic (PK) properties, with none reliably providing a reproducible and peakless pharmacodynamic (PD) effect that endures over 24 h from once-daily dosing. Insulin degludec is a novel acylated basal insulin with a unique mechanism of protracted absorption involving the formation of a depot of soluble multihexamer chains after subcutaneous injection. PK/PD studies show that insulin degludec has a very long duration of action, with a half-life exceeding 25 h. Once-daily dosing produces a steady-state profile characterized by a near-constant effect, which varies little from injection to injection in a given patient. Clinically, insulin degludec has been shown consistently to carry a lower risk of nocturnal hypoglycaemia than once-daily insulin glargine, in both basal+bolus and basal-only insulin regimens. The constancy of the steady-state profile of insulin degludec also means that day-to-day irregularities at the time of injection have relatively little PD influence, thereby offering the possibility of greater treatment flexibility for patients. © 2012 Blackwell Publishing Ltd.